2006
DOI: 10.1523/jneurosci.4106-05.2006
|View full text |Cite
|
Sign up to set email alerts
|

Small-Conductance Ca2+-Activated K+Channel Type 2 (SK2) Modulates Hippocampal Learning, Memory, and Synaptic Plasticity

Abstract: Apamin-sensitive, small-conductance, Ca 2ϩ -activated K ϩ channels (SK channels) modulate neuronal excitability in CA1 neurons. Blocking all SK channel subtypes with apamin facilitates the induction of hippocampal synaptic plasticity and enhances hippocampal learning. In CA1 dendrites, SK channels are activated by Ca 2ϩ through NMDA receptors and restrict glutamate-mediated EPSPs. Studies of SK channel knock-out mice reveal that of the three apamin-sensitive SK channel subunits (SK1-SK3), only SK2 subunits are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
221
1
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 190 publications
(236 citation statements)
references
References 41 publications
(65 reference statements)
13
221
1
1
Order By: Relevance
“…For example, the decrease in SK channel function following CIE treatment observed in many regions including the OFC would be expected to enhance synaptic efficacy and plasticity. In support of this, results from previous studies show that blocking these channels facilitates LTP and enhances learning and memory (Blank et al, 2003;Brennan et al, 2008;Hammond et al, 2006;Stackman et al, 2002), whereas overexpression of SK channels reduces LTP and impairs hippocampus-, amygdala-, and mPFC-dependent learning tasks. In addition to changes in glutamate receptor expression and function described above, alterations in dendritic Figure 8 Chronic intermittent ethanol (CIE) exposure suppresses the ability of the GlyT1 transport inhibitor sarcosine to reduce spiking in lateral orbitofrontal cortex (lOFC) neurons.…”
Section: Cie and Glutamatergic Signalingsupporting
confidence: 57%
“…For example, the decrease in SK channel function following CIE treatment observed in many regions including the OFC would be expected to enhance synaptic efficacy and plasticity. In support of this, results from previous studies show that blocking these channels facilitates LTP and enhances learning and memory (Blank et al, 2003;Brennan et al, 2008;Hammond et al, 2006;Stackman et al, 2002), whereas overexpression of SK channels reduces LTP and impairs hippocampus-, amygdala-, and mPFC-dependent learning tasks. In addition to changes in glutamate receptor expression and function described above, alterations in dendritic Figure 8 Chronic intermittent ethanol (CIE) exposure suppresses the ability of the GlyT1 transport inhibitor sarcosine to reduce spiking in lateral orbitofrontal cortex (lOFC) neurons.…”
Section: Cie and Glutamatergic Signalingsupporting
confidence: 57%
“…From in vitro studies, we identified several roles for KCa3.1 in microglial activation (Khanna et al, 2001;Kaushal et al, 2007), but its roles in astrocytes, neurons, and oligodendrocytes have not been addressed. Other SK channels (KCa2.2, KCa2.3) have been implicated in the slow afterhyperpolarization that regulates neuron firing frequency (Hammond et al, 2006;Faber, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…The current study did not clearly delineate relative contributions of K Ca 2.2 and 2.3 although K Ca 2.3 channels were found to be highly localized in the cell periphery, indicative of their function as plasma membrane ion channels. Although overexpression and suppression of K Ca 2.2 levels in genetically altered mice have been linked to pup viability (5,13,20), specific effects on gestation and parturition have not been reported. In fact, following suppression of K Ca 2.3 expression, the global K Ca 2 blocker apamin does not significantly alter uterine contractions (7), questioning any functional impact of other isoforms.…”
Section: Discussionmentioning
confidence: 99%